2022
DOI: 10.1101/2022.12.08.519630
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proximity labelling allows to study novel factors in chloroplast developmenta

Abstract: Chloroplast development is initiated by light-signals triggering the expression of nuclear encoded chloroplast genes in a first phase, followed by massive structural changes in the transition from proplastids to mature chloroplasts in the second phase. While the molecular players involved in the first phase are currently emerging, regulatory components of the second phase, demanding high plastid translational capacity and RNA processing, are still enigmatic. This is mostly due to the very limited amount of pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…We found that biotin labeling occurs in a substrate (Figure 1D) and time (Figure 1E) dependent manner. In contrast to higher plants where labeling saturation can be achieved by 50 µM biotin (Mair et al, 2019;Wurzinger et al), labeling in Chlamydomonas appears to saturate at a much higher biotin concentration of 2.5 mM. This is in line with work published in parallel in this issue where a 1 mM concentration was used (Kreis et al).…”
Section: Development Of Proximity Labeling In Chlamydomonas Reinhardtiisupporting
confidence: 79%
“…We found that biotin labeling occurs in a substrate (Figure 1D) and time (Figure 1E) dependent manner. In contrast to higher plants where labeling saturation can be achieved by 50 µM biotin (Mair et al, 2019;Wurzinger et al), labeling in Chlamydomonas appears to saturate at a much higher biotin concentration of 2.5 mM. This is in line with work published in parallel in this issue where a 1 mM concentration was used (Kreis et al).…”
Section: Development Of Proximity Labeling In Chlamydomonas Reinhardtiisupporting
confidence: 79%
“…In conclusion, TurboID-mediated PL has enabled the probing of known and new protein interaction networks in the nucleus, cytoplasm and at the plasma membrane of land plants with amazingly high sensitivity and specificity (Mair et al, 2019;Zhang et al, 2019;Arora et al, 2020;Xu et al, 2021;Tang et al, 2022). Our work and that of two parallel studies by Lau et al (2022) and Wurzinger et al (2022) add Chlamydomonas as another plant model and the chloroplast as another compartment amenable to the great power of TurboID-mediated PL. The availability of TurboID as a standard part in the Chlamydomonas MoClo tool kit, allowing its assembly with any bait in a single cloning step, will greatly facilitate PL in the community.…”
Section: What Do We Learn From the Obtained Proxiomes?mentioning
confidence: 73%
“…TurboID applications to identify protein-protein interaction networks in Arabidopsis and N. benthamiana used only 50-200 µM of exogenously added biotin but similar labeling times of 0.5-12 h, although strong protein biotinylation was observed already after as little as 15 min (Mair et al, 2019; Zhang et al, 2019; Xu et al, 2021; Tang et al, 2022; Wurzinger et al, 2022). While in these studies no effects on naturally biotinylated proteins was reported, we observed strong effects in Chlamydomonas with loss of natural protein biotinylation correlating with TurboID expression levels (Figures 2B, 2C, 3A, 4A; Supplemental Figure S7B).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TurboID applications to identify protein–protein interaction networks in Arabidopsis and N. benthamiana used only 50 to 200 µ M of exogenously added biotin but similar labeling times of 0.5 to 12 h, although strong protein biotinylation was observed already after as little as 15 min ( Mair et al 2019 ; Zhang et al 2019 ; Xu et al 2021 ; Tang et al 2022 ; Wurzinger et al 2022 ; Kim et al 2023 ). While in these studies no effects on naturally biotinylated proteins were reported, we observed strong effects in Chlamydomonas with loss of natural protein biotinylation that corresponded to TurboID expression levels ( Figs.…”
Section: Discussionmentioning
confidence: 99%